2010
DOI: 10.2139/ssrn.1819300
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Aspects of MSEs in MENA: Evidence from Egypt and Turkey

Abstract: This study attempts to shed light on the gendered aspect of MSEs (i.e. how the sectors of activities, income, growth, etc. differ by the gender of the entrepreneur) and tests some of the main claims of the rather modest available literature by means of an econometric analysis. The empirical work utilizes nationally representative MSE surveys conducted for Turkey and Egypt in 2001 and 2003 respectively (for brevity, we hereafter use "E&T" to refer to "Egypt and Turkey"). The working sample has 4136 and 4238 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In their study, Adly and Khatib (2014) reported that Egyptian women had a difficult time accessing finance from formal institutions such as banks. Thus, women entrepreneurs face a lack of capital and find themselves forced to use their own savings or family loans to finance the starting and support of their businesses (El Hamidi & Baslevent, 2010; Rudhumbu et al, 2020).…”
Section: Difficulties Faced By Women In Traditional Entrepreneurship:...mentioning
confidence: 99%
“…In their study, Adly and Khatib (2014) reported that Egyptian women had a difficult time accessing finance from formal institutions such as banks. Thus, women entrepreneurs face a lack of capital and find themselves forced to use their own savings or family loans to finance the starting and support of their businesses (El Hamidi & Baslevent, 2010; Rudhumbu et al, 2020).…”
Section: Difficulties Faced By Women In Traditional Entrepreneurship:...mentioning
confidence: 99%